La congelación de las líneas de base y de los límites marítimos de los Estados insulares en riesgo de perder la totalidad de sus respectivos territorios debido al aumento en el nivel del mar ocasionado por el cambio climático - Velásquez Barrionuevo, Alejandro José (2021)
This article presents the current problem of the sinking of the terrestrial spaces of certain insular states due to the rise in sea level caused by climate change. This problem led to the approval of the topic Sea-level rise in relation to international law in the programme of work of the United Nations International Law Commission, particularly in the area of statehood. The legal implications of the total sinking of the terrestrial space are analyzed in accordance with current international law, verifying that the final one is the loss of statehood. In order to solve the legal problem raised, the application of a legal fiction is proposed by which the baselines of the States at risk are considered frozen, which has already been presented as an issue to be studied in the aforementioned area by the International Law Commission.